Multimedia Communications and Video Coding
IX, 510 p.
Keywords: This book constitutes the proceedings of the International Symposium on Multimedia Communications and Video Coding (ISMCVC95) held October 11 - 13, 1995, at the Poly technic University in Brooklyn, New York. This Symposium was organized under the aus pices of the New York State funded Center for Advanced Technology in Telecommunications (CATT), in cooperation with the Communications Society and the Signal Processing Society of the Institute of Electrical and Electronic Engineers (IEEE). In preparing this book, we have summarized the topics presented in various sessions of the Symposium, including the keynote addresses, the Service Provider and Vendor Session, the Panel Discussion, as well as the twelve Technical Sessions. This summary is presented in the Introduction. 'Full papers submitted by the presenters are organized into eleven chapters, divided into three parts. Part I focuses on systems issues in multimedia communications. Part II concentrates on video coding algorithms. Part III discusses the interplay between video coding and network control for video delivery over various channels.